Benign Partial Nonrolandic Epilepsies - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
The syndrome of benign partial epilepsy with particular reference to the non-rolandic types is described and the relevant literature reviewed from the Pediatric Seizure Clinic and EEG Laboratory, Beilinson Medical Center, Petah Tikva, and the Sackler Faculty of Medicine, Tel Aviv University, Tel Aviv, Israel.